Revisiting Type 2‐high and Type 2‐low airway inflammation in asthma: current knowledge and therapeutic implications. Issue 2 (February 2017) - Robinson, D.; Humbert, M.; Buhl, R.; Cruz, A. A.; Inoue, H.; Korom, S.; Hanania, N. A.; Nair, P.
Summary: Asthma is a complex respiratory disorder characterized by marked heterogeneity in individual patient disease triggers and response to therapy. Several asthma phenotypes have now been identified, each defined by a unique interaction between genetic and environmental factors, including inflammatory, clinical and trigger‐related phenotypes. Endotypes further describe the functional or pathophysiologic mechanisms underlying the patient's disease. type 2‐driven asthma is an emerging nomenclature for a common subtype of asthma and is characterized by the release of signature cytokines IL‐4, IL‐5 and IL‐13 from cells of both the innate and adaptive immune systems. A number of well‐recognized biomarkers have been linked to mechanisms involved in type 2 airway inflammation, including fractional exhaled nitric oxide, serum IgE, periostin, and blood and sputum eosinophils. These type 2 cytokines are targets for pharmaceutical intervention, and a number of therapeutic options are under clinical investigation for the management of patients with uncontrolled severe asthma. Anticipating and understanding the heterogeneity of asthma and subsequent improved characterization of different phenotypes and endotypes must guide the selection of treatment to meet individual patients' needs.